2022
DOI: 10.1111/ipd.12939
|View full text |Cite
|
Sign up to set email alerts
|

Debonding of orthodontic appliance changes salivary physicochemical properties and favors regression of active caries lesions: A 13‐week follow‐up study

Abstract: Aim This prospective cohort study aimed to investigate whether orthodontic appliance removal (OAR) combined with caries‐preventive strategies and fluoride varnish treatments alters salivary physicochemical properties, changes the activity of carbonic anhydrase VI (CA VIACT) and α‐amylase (α‐AMLACT), and favors the regression of active caries lesions (ACL). Design Twenty‐two individuals aged between 13 and 24 years were assessed for the presence of visible biofilm, daily sugar exposure, caries activity, salivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Various studies have shown results similar to us in which they found a reduction in pH and buffer capacity (Kanaya et al 2007;Teixeira et al 2012) . Some other studies showed that there was an improvement in these parameters and especially in patients having a high caries index, there was an improvement in pH and buffering capacity (Peros et al 2011) (Cardoso et al 2022;Chang, Walsh, and Freer 1997) . Some authors have suggested a gradual increase in the salivary parameters and after a few months due to the adaptation of patients to orthodontic appliances these parameters tend to return to normal.…”
Section: Discussionmentioning
confidence: 88%
“…Various studies have shown results similar to us in which they found a reduction in pH and buffer capacity (Kanaya et al 2007;Teixeira et al 2012) . Some other studies showed that there was an improvement in these parameters and especially in patients having a high caries index, there was an improvement in pH and buffering capacity (Peros et al 2011) (Cardoso et al 2022;Chang, Walsh, and Freer 1997) . Some authors have suggested a gradual increase in the salivary parameters and after a few months due to the adaptation of patients to orthodontic appliances these parameters tend to return to normal.…”
Section: Discussionmentioning
confidence: 88%